Laju Respirasi Kecoak Jerman (Blattella germanica, Dictyoptera; Blattellidae) yang Resisten Terhadap Insektisida - Robby Jannatan; Resti Rahayu; Putra Santoso (Jurnal Biologi Universitas Andalas, 2013)
An experiment on respiration rate of German cockroach (Blattella germanica, Dictyoptera; Blattellidae) that had been resistant to pyrethroid insecticide was done from December 2012 to Mei 2013. This experiment used completely randomized design with two treatments (with insecticide and without insecticide exposured) and three replications. The respiration rate were measured using the Scholander Respirometer. The control subject were VCRU-WHO as a susceptible strain standarized by WHO, while the resistance strains were GFA-JKT, KRSA-BDG, PLZ-SMRD and PLZ-PDG consisted of female, male and nymph Individuals. The results shown that respiration rates were not significant difference between susceptible and resistance strains on females (F: 0.373, df: 4, P: 0.823), males (F: 0.562, df: 4, P: 0.696) and nymphs (F: 0.402, df: 4, P: 0.803). The respiration rate were also not significant difference between with insecticide and without insecticide exposured, except within GFA-JKT females (F: 9.161, df: 4, P: 0.039), VCRU-WHO males (F: 11.779, df: 4, P: 0.026) and GFA-JKT nymphs (F: 8.733, df: 4, P: 0.042). Those results support that resistant cockroach do not increase respiration rate in responding insecticide exposured. Keywords: German cockroach, respiration rate, strains, insecticide exposured